NH3 Gas Detection by Silicon Nanowire - Based Sensors - Nguyen, Khac Tung; Nguyen, Cong Tu; Nguyen, Huu Lam (Old Journal, 2019)
Gas sensors based on silicon nanowires were used to detect ammonia (NH₃) gas at working temperature, from room temperature to 100 °C. The silicon nanowires were grown on the Si (111) surface using thermal evaporation method with gold (Au) nanoparticles played as catalysts. The Si nanowires, which have an average diameter of 15-30 nm were formed at a temperature of 1100 °C for 60 min and using argon as carrying gas and a mixture of silicon and carbon powders (ratio 1:1) as a material source. The silicon nanowire – based gas sensors showed response to NH₃ gas, but non-response to water vapor, ethanol or acetone. The results of the sensor’s response showed that the NH₃ gas sensor had a high response at working temperature of 80 °C.